An Essay in Adaptive Reuse The Case of Bergama Küplü Hammam - Tuba Nur Baz; Müjgan Bahtiyar Karatosun (Iconarp International Journal of Architecture and Planning, 2017)
Bergama is an important settlement center which have different civilizations. Today, it comes forward with especially the cultural heritage of Antiquity but there is an important heritage which has Ottoman period’s impress too. The works which reflect to aqua culture effectuate a part of that heritage. Especially Turkish bath buildings have an important place to remind and sustain that culture.